Effect of Menopause on Quality of Life: Path Analysis from Ponorogo East Jawa - Chintya, Shally Ayu; Budihastuti, Uki Retno; Adriani, Rita Benya (Indonesian Journal of Medicine, 2019)
Background: Menopause is a biological process in women which is characterized by the cessation of menstruation and a decrease in hormone levels that cause symptoms that can affect quality of life. This study aims to determine the impact of menopause and other factors that influence the quality of life in women.Subjects and Method: This study was observational analytic with a case control approach. The study was conducted in six health centers in Ponorogo Regency, East Java in March to April 2019. The total sample of 225 women aged 40 to 64 years was divided between 2 grou included menopausal as case group and non-menopausal as control groups based on purposive sampling. The dependent variable was quality of life. The independent variables were menopause, hot flush, anxiety, insomnia, vaginal dryness, and family intimacy. Quality of life is measured by the SF-36 (Short Form Health Survey). Anxiety was measured by Depression Anxiety Stress Scales. Insomnia was measured by the Pittsburgh Sleep Quality Index. The collection of other variables was conducted using questionnaires and analyzed using path analysis.Results: The decrease in quality of life was directly and negatively affected by menopause (b = -0.72; 95% CI = -1.39 to -0.05; p = 0.034), hot flush (b = -0.72; 95% CI = -1.34 to -0.07; p = 0.028), insomnia (b = -0.79; 95% CI = -1.43 to -0.16; p = 0.014), anxiety (b = -1.75; 95% CI = -3.09 to -0.47; p = 0.011), and drought vagina (b = -1.01; 95% CI = -1.65 to -0.37; p = 0.002). Women with high family intimacy can improve quality of life and are positive (b = 1.32; 95% CI = 0.69 to 1.95; p <0.001).Conclusions: The decreased quality of life in women is directly affected by menopause, hot flush, insomnia, anxiety, and vaginal dryness. High family intimacy improves quality of life. Family flush, anxiety, and family intimacy have indirect effects on quality of life. Keywords: quality of life, menopause, path analysisCorrespondence: Shally Ayu Chintya, Public Health Master’s Program, Universitas Sebelas Maret. Jl. Ir. Sutami 36 A, Surakarta 57126, Jawa Tengah. Email: shallyayuchintya@yahoo.co.id. Mobile: 087702640660Indonesian Journal of Medicine (2019), 4(2): 155-164https://doi.org/10.26911/theijmed.2019.04.02.09